The association between resting metabolic rate and blood groups in overweight and obesity - Cecen, Serpil; Eren, Canan (Annals of Medical Research, 2021)
Aim: Obesity is characterized as increase of fat tissue due to energy imbalance in the body. Resting metabolic rate shows the energy required for vital functions at resting state, and varies individually. Resting metabolic rate is affected by many factors. The aim of this study was to investigate whether resting metabolic rate changes depending on the blood groups. Materials and Methods: A total of 185 females and 37 males aged between 17 and 72 years who were admitted to our outpatient clinic due to obesity were evaluated with bare feet in length. Weight, body mass index (BMI), fat percentage, fat mass, and fat free mass were determined by a bioimpedance device (Tanita-BC418). Resting metabolic rate was detected by a fitmate device. Calorimetric measurement method was used to measure resting metabolic rates (RMR). ABO and Rh blood groups were determined via Microplack method as Forward Reverse.Results: There was not any significant difference according to ABO blood groups in terms of age, gender, body weight, fat percentage (F%), fat mass (FM) fat free mass (FFM), fat mass index (FMI) and fat free mass index (FFMI). There was not any statistically significant difference for RMR, RMR% measurements according to ABO blood groups and Rh factor (p>0.05).Conclusion: Resting metabolic rate did not change according to the ABO blood groups and Rh factor in obese individuals. Since blood group antigens are variable parameters according to individuals, we did not find any meaningful finding in this study based on whether this variability has an effect on resting metabolic rate.
Keywords: ABO blood groups; obesity; resting metabolic rate, Rh factor